2021
DOI: 10.1111/hae.14303
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and magnetic resonance imaging for the detection of blood: An ex‐vivo study

Abstract: Objectives Early detection of bleeding into a joint is crucial in patients with haemophilia. This study was designed to evaluate the sensitivity of ultrasonography (USG) and magnetic resonance imaging (MRI) to detect the presence of blood in small concentrations in a simulated model to mimic joint bleeding. Materials and Methods Different concentrations of blood in plasma, varying from 0.1% to 45%, were collected in 10‐ml plastic syringes and imaged using 12 and 18 MHz USG transducers and with 1.5T and 3T MRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…As has been recently demonstrated in ex-vivo phantom studies, small quantities of blood can be missed on ultrasonographic examination, more often with 12 MHz probes (as in most POCUS devices) than with the more advanced 18 MHz probes. 18 Furthermore, it should be recognized that traces of blood in the joint can be enough to trigger inflammation, clinical symptoms and subsequent joint damage. 19 It is also a challenge to differentiate traces of fresh blood in an already haemorrhagic joint fluid from previous bleeds as is the case in many joints with chronic haemarthrosis.…”
Section: 11mentioning
confidence: 99%
See 1 more Smart Citation
“…As has been recently demonstrated in ex-vivo phantom studies, small quantities of blood can be missed on ultrasonographic examination, more often with 12 MHz probes (as in most POCUS devices) than with the more advanced 18 MHz probes. 18 Furthermore, it should be recognized that traces of blood in the joint can be enough to trigger inflammation, clinical symptoms and subsequent joint damage. 19 It is also a challenge to differentiate traces of fresh blood in an already haemorrhagic joint fluid from previous bleeds as is the case in many joints with chronic haemarthrosis.…”
Section: 11mentioning
confidence: 99%
“…Any radiological technique has its limit of detection and the same is true for ultrasonography. As has been recently demonstrated in ex‐vivo phantom studies, small quantities of blood can be missed on ultrasonographic examination, more often with 12 MHz probes (as in most POCUS devices) than with the more advanced 18 MHz probes 18 . Furthermore, it should be recognized that traces of blood in the joint can be enough to trigger inflammation, clinical symptoms and subsequent joint damage 19 .…”
Section: Diagnosis Of Haemophilia—defining the Disease Burdenmentioning
confidence: 99%
“…Ultrasound is increasingly used in addition to physical examination since it is a non-invasive method that can accurately assess joint effusion and changes in synovial tissue [ 11 , 14 16 ], it is widely available, and provides real-time information [ 11 , 14 16 ]. Moreover, previous studies have shown that ultrasonography is sensitive to differentiate between simple and complex joint effusion [ 17 , 18 ]. However, limitations of ultrasound are the operator dependency and therefore a substantial inter-observer variation of findings [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large haemarthroses may show fluid-fluid levels or thrombi on MRI. However, the accuracy of standard MRI protocols for the detection of early or minor joint bleeding has not been established yet [ 17 , 18 ]. Therefore, an accurate non-invasive reference standard to detect joint bleeding is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound can accurately assess the synovium, joint effusion, cartilage and joint bleeds. [11][12][13][14][15] In addition, ultrasound can detect synovial hypertrophy in joints without clinical symptoms. 16 Ultrasound is therefore recommended as an additional tool for diagnosing early joint bleeds and monitoring synovitis.…”
mentioning
confidence: 99%